A Methods engineering study on Samson Plastic Packaging and Contractual Services - Abarra, Geraldine L.; Lim, Angelito Jr.; Perez, Dianne (Diliman, Quezon City College of Engineering, 2001)
Samson Plastic Packaging and Contractual Services is a small-scaled manufacturing company involved in the production of plastic bags. Its three (3) major product lines are Polypropylene, High Density Polyethylene, and Linear Low Density Polyethylene plastic bags. The study addresses four major problems of the company : (1) Inefficient layout and working conditions; (2) Excessive scraps and rejects; (3) Lack of machine maintenance; (4) Lack of systems and procedures. For the problem of inefficient layout, two alternatives layouts were proposed; both are improving the working conditions of the company and reducing the distance to be traveled. Three proposals were given for the problem of excessive scraps and rejects. They are (1) have a standard set-up; (2) 24-hours, 7 days a week production; and (3) heating of machines on Sundays. For the problem of lack of machine maintenance, the group provided three plans of schedules : daily, weekly and monthly maintenance. Lastly, three flows of forms were specified for the problem of lack of systems and procedures. These proposed alternatives were evaluated using the Kepner-Tregoe Decision analysis. They were also evaluated according to their risks and costs. Based on the groups' analysis, the second proposed layout is best fit for the problem of inefficient layout and working conditions since it requires less distance to travel and less movement of materials. For the problem of excessive scrap, it is recommended that the company adopt a standard set-up for each product in this way, the trail and error attitude of the employees in getting the specification is eliminated. It is suggested that the company undergo regular weekly machine maintenance so as to prolong the life of its machines. Lastly, the group proposed new systems and procedures to be used by the company in order to improve its current status. A period of 7 weeks should be alloted for preliminary implementation. And the group suggests that there they company should employ a continuous improvement policy. Further more, a study on the raw materials should be conducted in order. Also, the company should have a further investigation on the acquisition of new and up-dated machines as well as the disposal of the two non-functioning extruding machines.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis